KOMUNIKASI STRATEGIS DALAM MEMBANGUN CITRA POSITIF SEKOLAH : PADA SEKOLAH DASAR ISLAM TERPADU AR RAJWAA SAMARINDA SEBERANG - Nihan Kristiyani; Sri Wartini; Widyatmike Gede Milawarman; Nurlaili; Masrur Yahya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research discusses strategic communication in building a positive image of the school implemented by the Ar Rajwaa Integrated Islamic Elementary School through the role of the public relations department.The method in this study uses a descriptive qualitative method, with observation techniques, information collection in the form of data, literature studies and interviews. The results of this study describe the strategic communication process carried out by the Ar Rajwaa Integrated Islamic Elementary School in interacting with students, educators and education staff and parents/guardians and the community so that they can build a positive image of the school. The strategic communication that was prepared was carried out in the form of Islamic communication, transparency and accountability, educational and positive content, and welcoming with hospitality at school. In addition to strategic communication, SD IT Ar Rajwaa carries out imagery through story telling, branding and alumni testimonials and has succeeded in gaining the trust of students' parents and the community. One of the proofs that public trust has been formed and the positive image of is that there are a number of prospective students who have been queuing to become students for the next 3 (three) years.